Research Progress on the Mechanism of Acupuncture in Treating Dysmenorrhea Caused by Endometriosis - Sun, Ningning; Su, Tongsheng (Journal of Contemporary Medical Practice, 2025)
The incidence of endometriosis (EMS) has increased significantly in recent years. As a common gynecological disease, its incidence rate among women of reproductive age can reach 10%-15% and shows a gradual upward trend. Dysmenorrhea is the most typical clinical manifestation of endometriosis; recurrent and progressive pain seriously affects women’s health and quality of life. Western medicine mainly relies on non-steroidal anti-inflammatory drugs, which have significant side effects. In contrast, there have been numerous studies on acupuncture for treating EMS-related dysmenorrhea, with remarkable efficacy. This article summarizes the clinical applications and relevant mechanisms of acupuncture, aiming to provide a reference for the promotion of acupuncture in the treatment of EMS-related dysmenorrhea.